Role of Toll-like Receptors Nine and Ten Polymorphisms in Childhood Bronchial Asthma Control and Their Relation to Cardiac Function - Rehab Ahmed Rabie; Asmaa Elsharkawy Hussien; Hesham Samy Abdelhameed; Soad Abdelsalam Shedeed; Noura Almadani; Hanaa A. Nofal; Dina S. El-Rafey; Hossam T. Ali; Mohammed Sanad Naguib (Diagnostics)
Background: Asthma is designated as the most widely spread chronic disease in children. Toll-like receptors (TLRs) are linked to several human diseases, including allergic diseases. We aimed to assess the link between TLR9 (rs187084) and TLR10 (rs11096956) gene polymorphisms and bronchial asthma and its control and their relation to respiratory and cardiac functions. Methods: This is a case-control study comprising 80 participants aged between 5 and 12 years old, divided into 20 healthy non-asthmatic participants and 60 asthmatic ones. The asthmatic group members were diagnosed clinically according to the diagnosis guidelines of The Global Initiative for Asthma (GINA) 2019 and subdivided according to GINA 2019 guidelines for asthma control into three subgroups (well-controlled, partially controlled, and uncontrolled). Genetic polymorphisms in TLR9 (rs187084) and TLR10 (rs11096956) were detected using real-time PCR. Results: We found a significant increase in TLR9 polymorphisms among asthmatic cases compared to the control (OR = 9.09 for the CT genotype and 5.24 for the TT genotype) and a similar increase in TLR10 polymorphisms (OR = 4.29 for the GT genotype and 10.71 for the TT genotype). Also, there was a significant increase in TLR9 and TLR10 polymorphisms among uncontrolled cases compared to both well-controlled cases and the control group. We discovered a significant association between TLR9 (rs187084) gene polymorphisms and pulmonary function tests (PFTs), with better results in the CC genotype. Additionally, a significant association with both RVFWSL (right ventricle free-wall longitudinal strain) and GLS (left ventricle global longitudinal strain apical 2-chamber view) with better values was linked to the CC genotype. Regarding TLR10 (rs11096956), there was a significant association between gene polymorphisms and PFTs, with better function in the GG genotype. Additionally, there was a significant association between TLR10 (rs11096956) gene polymorphisms and GLS AVG (left ventricle global longitudinal strain average), with the GG type having significantly better cardiac function. Conclusion: Subclinical cardiac dysfunction of the left and right ventricles was detected in asthmatic children. The CC genotype of TLR9 and the GG genotype of TLR10 are associated with better asthma control and better cardiac function. Therefore, TLR9 and TLR10 have a role in asthma control and cardiac dysfunction.